Activating Transcription Factor 3 Protects against Restraint Stress-Induced Gastrointestinal Injury in Mice - Chuang, Dun-Jie; Pethaperumal, Subhashree; Siwakoti, Bijaya; Chien, Hung-Jen; Cheng, Ching-Feng; Hung, Shih-Che; Lien, Te-Sheng; Sun, Der-Shan; Chang, Hsin-Hou (Cells (Basel, Switzerland), 2021)
Psychological stress increases the risk of gastrointestinal (GI) tract diseases, which involve bidirectional communication of the GI and nerves systems. Acute stress leads to GI ulcers; however, the mechanism of the native cellular protection pathway, which safeguards tissue integrality and maintains GI homeostasis, remains to be investigated. In a mouse model of this study, restraint stress induced GI leakage, abnormal tight junction protein expression, and cell death of gut epithelial cells. The expression of activating transcription factor 3 (ATF3), a stress-responsive transcription factor, is upregulated in the GI tissues of stressed animals. ATF3-deficient mice displayed an exacerbated phenotype of GI injuries. These results suggested that, in response to stress, ATF3 is part of the native cellular protective pathway in the GI system, which could be a molecular target for managing psychological stress-induced GI tract diseases.